2021
DOI: 10.1177/01945998211065656
|View full text |Cite
|
Sign up to set email alerts
|

OSA Treatment on Cardio‐ and Cerebrovascular Comorbidities: A Long‐term Nationwide Cohort Study

Abstract: Objective To compare the cardio- and cerebrovascular outcomes and survival rates of surgical and nonsurgical interventions for patients with obstructive sleep apnea (OSA) based on a national population-based database. Study Design Retrospective cohort study. Setting Taiwan National Health Insurance Research Database. Methods We analyzed all cases of OSA among adults (age >20 years and confirmed with ICD-9-CM) from January 2001 to December 2013. We compared the patients with OSA who received upper airway sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(69 reference statements)
0
5
0
Order By: Relevance
“…It remains unclear whether a longer follow‐up period may generate different outcomes. Third, it is essential for evaluating the value of any OSA treatment via investigating the cardio‐ and cerebrovascular outcomes of the patients 31,32 . Thus, further MISS MLS studies for patients with OSA in this field should be conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains unclear whether a longer follow‐up period may generate different outcomes. Third, it is essential for evaluating the value of any OSA treatment via investigating the cardio‐ and cerebrovascular outcomes of the patients 31,32 . Thus, further MISS MLS studies for patients with OSA in this field should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it is essential for evaluating the value of any OSA treatment via investigating the cardio-and cerebrovascular outcomes of the patients. 31,32 Thus, further MISS MLS studies for patients with OSA in this field should be conducted. Finally, no restrictions on the publish date were set.…”
Section: Literature Appraisals and Methodologymentioning
confidence: 99%
“…Sleep surgery is an effective alternative treatment for OSA, with improved cardiovascular and cerebrovascular outcomes compared to no treatment. 5 , 6 Previous studies with focus groups have found that patients with OSA desire more information about CPAP‐alternative treatment options from their providers. 7 …”
mentioning
confidence: 99%
“…Sleep surgery is an effective alternative treatment for OSA, with improved cardiovascular and cerebrovascular outcomes compared to no treatment. 5,6 Previous studies with focus groups have found that patients with OSA desire more information about CPAP-alternative treatment options from their providers. 7 Despite the internet being an important source of information for patients who are researching sleep surgery, there is a dearth of information regarding the quality of the online materials available for patients interested OSA surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation